Understanding the European Commission's use of politicisation in the negotiation of interinstitutional agreements: the role of consultations and issue framing. Issue 3 (3rd March 2020) - Bunea, Adriana
ABSTRACT: The negotiations that precede the adoption of EU interinstitutional agreements present relevant opportunities for political entrepreneurs to politicise the interinstitutional dialogue. This study asks when and how does the European Commission politicise the negotiations of EU interinstitutional agreements? Building on a classic model explaining the politicisation of EU at domestic level, the study argues that the Commission has incentives to politicise negotiations when these revolve around substantive agreements that propose relevant change, when it anticipates autonomy or power losses and opposition on behalf of negotiations counterparts. Politicisation is used as a tool for re-legitimisation with a view to strengthening the power to shape negotiation outcomes. Stakeholder consultations and issue framing are instruments used to deploy classic politicisation strategies of expanding publicity, the universe of actors and controversy. The study shows how the Commission politicised the negotiations of two most recent agreements on a mandatory Transparency Register and Better Law-making.